Allopatric speciation with little niche divergence is common among alpine Primulaceae. (20th October 2015) - Boucher, Florian C.; Zimmermann, Niklaus E.; Conti, Elena
Abstract: Aim: Despite the accumulation of cases describing fast radiations of alpine plants, we still have limited understanding of the drivers of speciation in alpine floras and of the precise the timing of their diversification. Here, we investigated spatial and temporal patterns of speciation in three groups of alpine Primulaceae. Location: Mountains of the European Alpine System. Methods: We built a new phylogeny of Primulaceae including all species in three focal groups: Androsace sect. Aretia, Primula sect. Auricula and Soldanella . Combining phylogenetic information with a detailed climatic data set, we investigated patterns of range and ecological overlap between sister‐species using an approach that takes phylogenetic uncertainty into account. Finally, we investigated temporal trajectories of diversification in the three focal groups. Results: We found that a large majority of sister‐species pairs in the three groups are strictly allopatric and show little differences in substrate and climatic preferences, a result that was robust to phylogenetic uncertainty. While rates of diversification have remained constant in Soldanella, both Androsace sect. Aretia and Primula sect. Auricula showed decreased diversification rates in the Pleistocene compared to previous geological epochs. Main conclusions: Allopatric speciation with little niche divergence appears to have been by far the most common mode of speciation across the three groups studied. A few examples, however, suggest that ecological and polyploid speciation might also have played a role in the diversification of these three groups. Finally, extensive diversification likely occurred in the late Miocene and Pliocene coinciding with the later phases of the Alpine uplift, while diversification slowed down during subsequent glacial cycles of the Pleistocene.